Design and analysis of intelligent HES mental health treatment ship - Shahrizan Jamaludin; Tawheed Hasan; W.B. Wan Nik (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mental health is a very important issue for many reasons. Unfortunately, developing countries hardly place much importance on it. People living among us—1 in 5 people—have a mental health issue. But very little importance is given to it. As a result, small problems later create big crises. Residents living far from cities are further behind in these mental health treatments. This research aims to ensure this basic mental health treatment is available to people living in remote areas. Work is being done here for them, where it is not easy to come to the hospital. Unfortunately, not all cities have qualified doctors to treat mental problems. The result is suffering. Post-Covid-19, this problem has become even bigger. This research project is being worked on to give them the minimum treatment. This ship goes to the river’s wide area. People there are examined for mental issues and given appropriate treatment. A special ship has been built for this purpose. Keeping in mind the global energy crisis, the facilities of this ship have been provided with sunlight. The ship will have all the necessary medical facilities run by solar energy instead of fuel. Here is a detailed analysis of the operations of this project.